Freaky Friday - Waters, Mark (Pasig City : Viva Video, 2004)
Jamie Lee Curtis and Lindsay Lohan star in FREAKY FRIDAY, the hilarious and delightful comedy everyone will love. Dr. Tess Coleman (Curtis) and her teenage daughter Anna (Lohan) have one thing in common- they don't relate to each other on anything. Not clothes or hair, or men or Anna's rock band aspirations. Nothing. After one particularly explosive Thursday evening, a little mystic mayhem changes their lives. They wake up Friday to the biggest freak-out ever - Tess and Anna are trapped inside each other's body. Literally forced to walk in each other's shoes, they gain respect and understanding for the other's point of view. But Tess's wedding is Saturday, and the two must find a way to switch back. And fast. Filled with comedy, rockin' music and heart, FREAKY FRIDAY is freaking fun.